2018
DOI: 10.1093/cid/ciy347
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Patients Lost to Follow-up in African Antiretroviral Therapy Programs: Individual Patient Data Meta-analysis

Abstract: Retention on antiretrovirals is of concern in Africa. We analyzed outcomes in patients lost to follow-up: at 4 years after last contact, 22% had died, 23% had stopped therapy, 15% were in another clinic, and 32% could not be found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
77
4
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(87 citation statements)
references
References 47 publications
5
77
4
1
Order By: Relevance
“…Our study has some limitations. First, we are likely to have overestimated loss to follow‐up as several studies have demonstrated high mortality and “silent transfers” to other clinics among people not retained in care in LMICs [18]. As we used routinely collected data from eight clinics, we were unable to search for silent transfers to other clinics, and did not have consent to search for deaths on the national registry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study has some limitations. First, we are likely to have overestimated loss to follow‐up as several studies have demonstrated high mortality and “silent transfers” to other clinics among people not retained in care in LMICs [18]. As we used routinely collected data from eight clinics, we were unable to search for silent transfers to other clinics, and did not have consent to search for deaths on the national registry.…”
Section: Discussionmentioning
confidence: 99%
“…Patients whose records stated “transferred out” to another clinic were not defined as lost to follow‐up, but were censored on the day of last visit. We combined lost to follow‐up and death, as death is poorly recorded in the TIER.net register, and there is evidence that a significant proportion of patients lost to follow‐up in ART programmes have died [18].…”
Section: Methodsmentioning
confidence: 99%
“…Similar levels of transfers have been reported other African studies. In an individual patient data meta‐analysis of nine tracing studies conducted in SSA, 15% of the patients had transferred to another facility at the third year . A previous study cited the decentralisation of treatment and the proximity to new health facility offering ART as the main reason for transferring .…”
Section: Discussionmentioning
confidence: 99%
“…In our cohort this number was even higher in those with EPTB diagnosis. A recent meta-analysis including data of 7,377 patients who started cART and were subsequently LTFU showed a rate of 21.8% of subjects to be deceased while 14.8% of patients LTFU have been transferred to another clinic [46]. Factors associated with poor outcome in patients with EPTB in our study were age of >45 years and not being on cART.…”
Section: Discussionmentioning
confidence: 51%